Joining processes for dissimilar and advanced materials - Rakesh, Pawan; Davim, J. Paulo (Woodhead Publishing, 2021)
Joining Processes for Dissimilar and Advanced Materials describes how to overcome the many challenges involved in the joining of similar and dissimilar materials resulting from factors including different thermal coefficients and melting points. Traditional joining processes are ineffective with many newly developed materials. The ever-increasing industrial demands for production efficiency and high-performance materials are also pushing this technology forward. The resulting emergence of advanced micro- and nanoscale material joining technologies, have provided many solutions to these challenges. Drawing on the latest research, this book describes primary and secondary processes for the joining of advanced materials such as metals and alloys, intermetallics, ceramics, glasses, polymers, superalloys, electronic materials and composites in similar and dissimilar combinations. It also covers details of joint design, quality assurance, economics and service life of the product.
Keywords: Joints (Engineering); Materials.; elektronické knihy; electronic books